Analisis Sistem Pengelolaan Proyek Investasi Dengan Dana PMN APBN Di PT Pal - Elsaday Rita Vierensa Ambarita; Astrini Aning Widoretno (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to evaluate the suitability of the investment project management system at PT PAL Indonesia with internal control components. This research uses a qualitative approach by describing the data descriptively. Data were collected through interviews and observations as information collection methods. This research was conducted directly at PT PAL Indonesia to collect primary data as part of field research. The results showed that the Investment Project Management System with APBN PMN Funds was in accordance with the internal control components.